High prevalence of confirmed, but also of potential and believed, neuropathic pain in pain clinics. (24th August 2012) - Pérez, C.; Ribera, M.V.; Gálvez, R.; Micó, J.A.; Barutell, C.; Failde, I.; Sánchez‐Magro, I.; Stern, A.
Abstract Background and aims Epidemiological data about neuropathic pain are still scarce. A national survey, based on neurologic clinical diagnosis, was performed to determine its prevalence among patients attending pain clinics. Methods An epidemiological cross‐sectional study involving pain clinics across all regions in Spain was carried out. Pain specialists evaluated the medical files and the clinical condition of patients attending their practices systematically during 1 day. They used the revised definition and grading system proposed in 2008 to decide whether a given patient had definite (i.e., confirmed), probable (potential) or possible (believed) neuropathic pain. Also, they provided a diagnostic label for neuropathic pain conditions and appraised treatment adequacy. Results In a single day, 178 pain specialists provided data from 2173 patients. Definite, probable and possible neuropathic pain was cited in 639 (29.4%), 304 (14.0%) and 97 (4.5%) patients, respectively. Almost two‐thirds of these were women. A diagnostic label of primary pure central and/or peripheral neuropathic pain was cited in 344 (15.8%) patients. The most common diagnostic label (568 patients) was low back pain or sciatica causing mixed neuropathic pain. Definite neuropathic pain diagnosis was less likely in patients with mixed pain conditions and in women derived from primary care. Co‐morbid depressive or anxiety symptoms were usual. Conclusions Definite (confirmed) neuropathic pain alone was as prevalent as neuropathic pain ascertained with screening questionnaires in prior recent European studies. The clinical relevance of the surplus of patients with potential and believed neuropathic pain ascertained by clinicians is uncertain.